The role of cuproptosis in the occurrence and development of gastric cancer - Lu, Ling; Yang, Wenhui; Gu, Yuning; Jin, Longtao; Liang, Zhaofeng (Frontiers in Pharmacology, 2025)
Gastric cancer has emerged as a major global public health threat due to its high incidence and mortality rates. Despite advances in diagnostic and therapeutic approaches, treatment outcomes remain unsatisfactory with frequent disease recurrence and poor prognosis. This underscores the urgent need to develop novel therapeutic strategies against gastric cancer. Cuproptosis, a novel form of cellular death, has garnered increasing attention from researchers regarding its relationship with the onset and progression of gastric cancer. This article aims to explore the molecular mechanisms of cuproptosis, its functions in gastric cancer, and its potential therapeutic applications. We analyze the driving factors and defense mechanisms of cuproptosis, as well as how it influences the growth, metastasis, and drug resistance of gastric cancer cells. Furthermore, we discuss the interplay between cuproptosis and the gastric cancer microenvironment, and consider the possibilities of this mechanism in future clinical treatments.